Negative and Positive PlaySpace in Treasure Island - Sally Bushell (Barnelitterært Forskningstidsskrift)
This paper explores the concept of PlaySpace for literature as a shared spatial structure generated out of the adult-child dynamic at the heart of Children’s Fiction. It counters the negative dynamic between adult and child articulated by Rose, Lesnik-Oberstein and others, with a positive spatial dynamic for imaginative play and growth in which the child needs the adult as much as the adult needs the child. This shared space can function both positively and negatively. If PlaySpace requires the necessary frame of a protective adult for the child to be spatially secure, and thus play freely, then what happens when that figure is not present or turns out not to be what he or she appeared to be? The second half of the paper explores the concept further in relation to Robert Louis Stevenson’s Treasure Island, one of the earliest examples of fiction explicitly written for a child readership as a “story for boys” (Stevenson, [1894] 1925, p. 123). Treasure Island immediately problematises this psycho-spatial dynamic in and through Jim’s relationship to the island, and the reader’s relationship to Jim.